Extraction of aromas from Pistacia lentiscus L. leaves using alternative solvents: COSMO-RS-assisted solvent screening and GC-MS metabolites profiling. Issue 4 (3rd March 2020) - Chaabani, Emna; Abert Vian, Maryline; Bott, Romain; Ginies, Christian; Defoort, Catherine; Ksouri, Riadh; Chemat, Farid
ABSTRACT: This study aimed to evaluate the extraction efficiency of six alternative solvents compared to hexane, conventionally used, for extraction of aromas from herbs and spices. It has been performed through theoretical approach using conductor-like screening model for real solvents (COSMO-RS) as predictive method and experimental approach based on gas chromatography–mass spectrometry (GC-MS) analysis paired with multivariate statistical analysis. Differences between theory and experiments have been noticed for cyclopentyl methyl ether (CPME) that appeared a good candidate in theory but gives the lowest extraction yield (14.12 g/L). Ethyl acetate (EtOAc) exhibited the highest extraction yield (18.74 g/L) and could be the most promising solvent to substitute hexane for aromas extraction from Pistacia. lentiscus L . leaves. Graphical abstract: